PARTISIPASI PEMILIH DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI SINTANG TAHUN 2024 - Mahin, Mikael (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Abstract: This study is about voter participation in the 2024 Sintang Regent and Deputy Regent election. Voter participation in a democratic country is an important aspect for the implementation of the highest legitimate state power by the people (people's sovereignty), which is manifested in their involvement in the democratic party. The purpose of this study is to determine Voter Participation in the 2024 Sintang Regent and Deputy Regent Election. The research approach used in this study is a qualitative descriptive method with a literacy study. Researchers collect relevant information from various sources such as books, journals, news portals and social media. The information is then quoted, analyzed and summarized to become a complete research result. The results of the study show voter participation in the election of the Regent and Deputy Regent of Sintang Regency in 2024, the number of voters in the Permanent Voter List (DPT) is 320,813 voters and the number of voters is 256,767 voters. Keywords: Participation, Voters, Election of Regent and Deputy Regent.